2007
DOI: 10.1016/j.enpol.2007.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Energy comes home

Abstract: Abstract:The growth in private energy consumption is an increasing problem in the Western countries. From an environmental point of view, this consumption has to be reduced.This article discusses private energy consumption and possibilities for reduction in Norway, with a special focus on the home. It argues against a rational economic view of the consumer and emphasizes the significance of a more subtle understanding of private energy use. The article approaches the challenges of reducing private energy consu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
136
0
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 13 publications
3
136
0
5
Order By: Relevance
“…Similar to practice theory, the later developments of the domestication model stress how technology is appropriated in both reciprocal and simultaneous negotiations. It offers insight into changes that take place with respect to human beliefs and actions, as well as with respect to technology and the material environment (Aune 2007;Ryghaug et al 2011). Technologies must align with pre-existing routines, practice, identities, and values if they are to be accepted.…”
Section: The Practice Of Domesticating Technologymentioning
confidence: 99%
“…Similar to practice theory, the later developments of the domestication model stress how technology is appropriated in both reciprocal and simultaneous negotiations. It offers insight into changes that take place with respect to human beliefs and actions, as well as with respect to technology and the material environment (Aune 2007;Ryghaug et al 2011). Technologies must align with pre-existing routines, practice, identities, and values if they are to be accepted.…”
Section: The Practice Of Domesticating Technologymentioning
confidence: 99%
“…Such Domestication, then, is a process wherein the employment of technological objects and the understanding of scientifically described phenomena (such as energy efficiency or climate change) may be modified or transformed. In this manner, domestication analysis offers insight into changes that take place with respect to the human actions and the sense-making that are at the core of energy cultures (Aune, 2007). Outcomes of domestication may consequently be understood as micro-networks of humans, artifacts, knowledge and institutions.…”
Section: Energy Cultures and The Domestication Of Energy: Conditions mentioning
confidence: 99%
“…Previous studies have identified the dominant position of energy cultures that privileges comfort and convenience (Aune, 1998(Aune, , 2007Shove, 2003). Since energy cultures have been shown to be solidly embedded in everyday life practices, they have also been considered robust and fairly resistant to change (e.g., Stephenson et al, 2010;Gram-Hanssen, 2011).…”
Section: Conclusion: Changed Meaning Resilient But Troubled Practicementioning
confidence: 99%
See 1 more Smart Citation
“…As early as 1985, Wilk and Wilhite described the rationality of not investing in home insulation that is revealed if competing normative goals that are particularly abundant only in domestic settings are taken seriously (see, e.g., Aune, 2007). Extending this perspective, Shove (1998) reminded us that the individuals involved in (not) making energy-efficient choices are creative social agents embedded in a broad variety of technical, social and cultural contexts that have to be accounted for if these (non) investments are studied.…”
Section: Factors Explaining the Energy Efficiency Paradoxmentioning
confidence: 99%